The functions of land in irrigation in Serbia - Nataésa Kljajić; Nada Mijajlović; Slavica Arsić (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
Land represents one of the key factors limiting crop production due to the simultaneous action of two processes as demand for food increasing, on the one hand, and reducing the area of agricultural land, on the other. Production capacity of the land reduces the continuous processes and damages toward agricultural areas. Of the total available land of approximately 8.8 million ha, agricultural land in the Republic of Serbia covers 5.9 million ha, of which 4.7 million ha represents arable land, and 3.7 million hectares are fields. Since not all arable land is suitable for irrigation, 3.6 million ha are of that kind. So, Serbia has around 0.4 ha of arable land per capita and the land fund is constantly decreasing. This small area should provide enough food for the population. Accordingly, this paper shows the structure of agricultural land, irrigated area in ha and their percentages, area under different irrigation systems (surface, spraying, dripping) and area of arable land covered with gardens, orchards, vineyards and meadows, in the period 2000-2010. At the end of the paper tables are given showing areas where irrigation is applied under different crops in 2010.
Keywords: 330; rural development; land use; irrigation; protection